Occupational health outcomes for workers in the agriculture, forestry and fishing sector: Implications for immigrant workers in the southeastern US. Issue 8 (28th February 2013) - Quandt, Sara A.; Kucera, Kristen L.; Haynes, Courtney; Klein, Bradley G.; Langley, Ricky; Agnew, Michael; Levin, Jeffrey L.; Howard, Timothy; Nussbaum, Maury A.
Abstract Background Workers in the Agriculture, Forestry, and Fisheries (AgFF) sector experience exposures directly related to the work itself, as well as the physical environment in which the work occurs. Health outcomes vary from immediate to delayed, and from acute to chronic. Methods We reviewed existing literature on the health outcomes of work in the AgFF sector and identified areas where further research is needed to understand the impact of these exposures on immigrant Latino workers in the southeastern US. Results Outcomes related to specific body systems (e.g., musculoskeletal, respiratory) as well as particular exposure sources (e.g., pesticides, noise) were reviewed. The most extensive evidence exists for agriculture, with a particular focus on chemical exposures. Little research in the southeastern US has examined health outcomes of exposures of immigrant workers in forestry or fisheries. Conclusion As the AgFF labor force includes a growing number of Latino immigrants, more research is needed to characterize a broad range of exposures and health outcomes experienced by this population, particularly in forestry and fisheries. Am. J. Ind. Med. 56:940–959, 2013. © 2013 Wiley Periodicals, Inc.